Isolated 6th cranial nerve palsy: a rare manifestation of tuberculosis - Kantharia, Shehnaz; Kantharia, Rajesh A.; Reddy P., Pradeepkran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Tuberculosis (TB) is a contagious infection that is usually caused by Mycobacterium tuberculosis bacteria. It usually affects the lungs and also spreads to the brain and spine. In the central nervous system, the neurological manifestations are numerous and varied and usually occur in two major forms, tuberculous meningitis and tuberculoma. Tuberculoma are well defined, granulomatous, space occupying lesions, which can occur anywhere in the central nervous system. Usually, brainstem tuberculoma can cause sixth and seventh cranial nerve affections along with motor and sensory symptoms, which are usually unilateral. Isolated abducens nerve palsy could be attributed to lesions of the nerve along their extra axial course and cause diplopia. Here we are presenting a case report of an 18-year-old boy with isolated sixth nerve palsy due to tuberculosis. The diagnosis of tuberculosis was achieved using interventional radiology for the purpose of biopsy. Using an image guided technique, we could avoid an open surgical procedure.